Bibliometric Analysis of Eco-design Research and Socio-Scientific Issues in Environmental Learning: A Study with VOSviewer to Strengthen Eco-Literacy and Critical Thinking Skills - Evita Anggereini; Ervan Johan Wicaksana; Afreni Hamidah; Muswita (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to map and analyze research trends on Eco-design and Socio-Scientific Issues (SSI) in environmental learning through bibliometric analysis. Data were collected from the Scopus database covering publications from 2013 to 2024 related to Eco-design, SSI, environmental education, eco-literacy, and critical thinking. Bibliometric data were analyzed using VOSviewer software to visualize research networks including co-authorship, co-occurrence (keywords), citations, co-citations, and overlay analysis. The findings revealed four main research clusters linking environmental education, SSI, Eco-design, eco-literacy, and critical thinking. The results also show that research has evolved from descriptive studies to a more integrative and application-oriented approach that combines design innovation with socio-scientific reflection. The overlay visualization shows a temporal shift from early themes such as environmental awareness to a more recent emphasis on sustainability, critical thinking, and ecological literacy. These results highlight that the integration of Eco-design with SSI promotes a transformative paradigm in environmental education by connecting ethical and scientific perspectives with real-world solutions. This study provides a conceptual foundation for developing an interdisciplinary learning model that strengthens students' ecological literacy and critical thinking skills in sustainability-oriented education.